Meta-Analysis of Effective Management Strategies for Malignant Central Airway Obstruction - Putri, Septriana; Yessy Susanty Sabri; Fenty Anggrainy (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Malignant central airway obstruction (MCAO) significantly impacts the quality of life and prognosis of patients with advanced lung cancer or metastatic disease. This meta-analysis aims to evaluate the effectiveness and safety of various management strategies for MCAO. Methods: A systematic search of PubMed, Embase, and Cochrane databases from 2018 to 2024 was conducted to identify randomized controlled trials (RCTs) and observational studies comparing different MCAO management approaches. Primary outcomes included improvement in airway patency, dyspnea scores, and survival. Secondary outcomes included procedural complications and quality-of-life measures. A random-effects model was used to pool data, and heterogeneity was assessed using the I² statistic. Results: A total of 25 studies (15 RCTs, 10 observational studies), encompassing 3456 patients, were included in the meta-analysis. Interventions assessed were rigid bronchoscopy with various modalities (e.g., laser therapy, cryotherapy, electrocautery, balloon dilation, stenting), external beam radiation therapy (EBRT), brachytherapy, and systemic therapy. Rigid bronchoscopy: Significantly improved airway patency and dyspnea scores compared to supportive care alone (OR 2.86, 95% CI 1.95-4.18; p<0.001). Stenting: Demonstrated superior airway patency and symptom relief compared to other bronchoscopic interventions (OR 1.73, 95% CI 1.21-2.48; p=0.003). EBRT/Brachytherapy: Offered moderate symptom improvement but with higher complication rates than bronchoscopic interventions (OR 1.39, 95% CI 1.05-1.85; p=0.021). Systemic therapy (chemotherapy/immunotherapy): Provided limited benefit in terms of airway patency but may impact overall survival in specific tumor types. Conclusion: Rigid bronchoscopy, particularly with stenting, is the most effective initial management strategy for MCAO, providing rapid symptom relief and airway recanalization. EBRT/brachytherapy can be considered as adjuncts or alternatives in select cases. Further research is needed to determine the optimal combination and sequencing of therapies for different tumor types and stages.